Russian Aviation Pilots - Washington State University Vancouver Library; http://library.vancouver.wsu.edu/ (1968)
A photo of a postcard of three Russian aviation pilots, Beliakoff- navigator, Chekaloff- pilot, and Baidukoff, co-pilot, are in the top left of a larger photo showing a Russian aircraft sitting on a field before a large crowd. The photo was taken on January of 1963 and reads ""Russian North Pole Fliers at Pearson Field, Vancouver, WA, just after arriving from Moscow, June 20, 1937"". 5 x 3.5 in.